(untitled) (Global Journal of Human-Social Science, 2019)
Samuel P Huntington s Clash of Civilization receives a recognition to analyze world politics To defend this concept Edward Said s clash of Ignorance by finding out a root cause of the clash takes the place of harmony between civilizations In this connection we have seen that E M Forster s A Passage to India upholds the clash of civilizations-Indians and the English for cultural difference supporting Huntington s theory as well as for ignorance hatred and mentality supporting Said s concept through the story development and character analysis So this paper has attempted to analyze this novel and tries to show not only for the cultural difference but also for any other causes civilizational crisis can occur This paper also presents the soul bonding universal brotherhood proper understanding can be a bridge between civilizations